The Effect of Green Banking Implementation and Financial Performance on Bank Profitability in Indonesia - Tampikalih, Satia; Syafri, Syafri (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the effect of green banking implementation and financial performance on the profitability of commercial banks in Indonesia in the period 2013-2023. This research uses a quantitative descriptive approach with secondary data obtained from the annual reports of eight commercial banks and other relevant literature. Data analysis was conducted using panel data regression, with the best model selection through Chow and Hausman tests. The results showed that GBDI, NPL, and BOPO had a significant negative effect on ROA. GBDI, which should encourage profitability, has a negative impact, indicating that the implementation of green banking is not optimal and requires time and long-term adaptation strategies. CAR and LDR did not show a significant effect on ROA. In conclusion, bank profitability in Indonesia has not been fully driven by green banking practices and other financial indicators consistently. Therefore, sustained commitment and a more comprehensive implementation strategy are needed to make green banking a sustainable driver of profitability.